Comparative Studies of Air Pollution Modelling Techniques from a Point Source(s) of a Thermal Power Plant - Rahil, Changotra (My University, 2014)
Increase in technological, industrial and agricultural advancement, coupled with increase in population growth, has deteriorated the air quality throughout the different cities of the world. Rapidly growing cities, more traffic on roads, growing energy consumption, waste production and lack of strict implementation of environmental regulation are the reasons for the increase in the discharge of pollutants into the atmosphere. People are entirely dependent on continuous supply of energy for most of the everyday activities, therefore, in order to meet this increasing demand on energy, government and private sectors are investing huge amount of money in energy production, especially on electricity generation. Electricity generation through thermal power plants (TPPs) in India has increased manifold in the recent decades to meet the demand of the increasing population. Combustion process in TPPs converts coal into useful heat energy, but it also emits carbon dioxide (CO2), sulphur oxides (SOx), nitrogen oxides (NOx); CFCs besides air borne inorganic particulates, such as fly ash and suspended particulate matter (SPM). Thus, Thermal Power Plants (TPPs) have been found to affect air quality of the surrounding region adversely. In the present study, attempt has been made to compare two air quality dispersion models in predicting the air quality by taking into account the emissions of thermal power plant. The emission inventory was prepared for Rajpura Thermal Power Plant. Stack monitoring was carried out to monitor the emissions from the thermal power plant and additional emission inventory was prepared for two other large scale industries in the study area to differentiate the effect of thermal power plant alone. Mean hourly meteorological data for one year period January, 2013 to December, 2013 was collected from Weather Monitoring Station and Upper air for the same year was collected from IMD, Pune which was imported to RAMMET View and AERMET View. Based on wind data, population density, topography and other local parameters of study area eight receptors were selected on which maximum incremental Ground Level Concentrations (GLCs) of SO2, NO2 and SPM were predicted by using EPA approved dispersion models; namely ISCST3 and AERMOD. GLCs predicted by two models were compared and the models were validated with the results of actual ambient air monitoring at the receptors site. The spatial distribution of the maximum incremental concentration for the point sources of TPP shows AERMOD predicted higher incremental concentrations near to the source as compared to ISCST3 for annual and daily (24 h) averaging periods. Considering additional major industrial sources, the predicted GLCs of both the models were almost similar to the results as predicted during the modelling of TPP alone. Thus, results depicts that the major source of air pollution in the region is Thermal Power Plant. Validation of models prediction with ambient air measurements was done for both ISCST3 and AERMOD and the models were observed to underestimate the observed ground level concentration of NO2 and SO2 for the nearby receptors to the thermal power plant and for SPM; predictions of both ISCST3 and AERMOD were underestimating the observed ground level concentration of SPM at all the receptors. This is probable because the building downwash and emission from mobile sources were not taken into consideration in the models run. Overall results of AERMOD seem to be good in correlation graphs when compared to ISCST3 with higher coefficient of correlation value for AERMOD. Thus, AERMOD model is more validate and accurate in predicting the GLCs at various receptors.
M.Tech (EST) Dissertation
Keywords: Air pollution; Modelling; AERMOD; ISCST3